Fenomena Bunuh Diri, Etika Sosial, Sunyata Buddhisme dan Posisi Gereja Katolik Dalam Sorotan Filsafat Manusia - Kelen Donatus, Sermada; Olla, Paulinus Yan; Abner Hubertus (Seri Filsafat Teologi, 2024)
Suicide is a human phenomenon occurring rapidly nowadays. The purpose of writing this article is to present what is the essence of human being under the frame of certain anthropological philosophical views, and what impact derived from the philosophical views has been put on the social ethics, especially on the position of catholic church toward suicide. The method the author has used is the way of describing some cases of suicide, considering them carefully in the light of social ethics with the back ground of philosophical concepts, especially ??nyat? philosophy of Buddhism. The conclusion taken out from the elaboration of this theme is that moral judgement as proposed by the catholic doctrine concerning suicide depends totally on the philosophical concepts about the essence of human being